Entrepreneurial proposal: an english language training course for the tourism sector in the coffee region (2022)
Colombia is characterized by its extractivist economy in which the sale of minerals is the main source of income, however, some attempts have been made to potentiate national tourism as another economic field. For this reason, the Colombian government has offered courses focused on turism with its institution SENA and other institutions which train tourism employees in this field. In terms of English language instruction, some private and public institutions have offered courses that are broad in the sense that all workers receive the same language instruction. This project is relevant since it will provide specialized English instruction courses for restaurants, travel agencies, hotels in the following municipalities: Santuario, Anserma, Dosquebradas, and Pereira. These courses will be offered to tourism employees with a maximum of 15 students per group. Each course will intend to achieve a B1.1 level with a duration of 17 weeks (102 hours per course). The design of the courses will work under the theory of socio-constructivism as this will boost collaborative work through the use of real-life situations. Additionally, the ESP approach will play an essential role in the lessons as the target content focuses on what they really need in their work setting. The expected results are: 1) to provide the learning tools for students to achieve B1 level; 2) to provide small businesses with the capability to interact with foreing tourists; 3) to help tourism employees understand intercultural differences and how to assertively interact with tourists.